2015
DOI: 10.1371/journal.pone.0133428
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inhaled Corticosteroids on Growth in Children with Asthma: Systematic Review and Meta-Analysis

Abstract: BackgroundLong-term inhaled corticosteroids (ICS) may reduce growth velocity and final height of children with asthma. We aimed to evaluate the association between ICS use of >12 months and growth.MethodsWe initially searched MEDLINE and EMBASE in July 2013, followed by a PubMed search updated to December 2014. We selected RCTs and controlled observational studies of ICS use in patients with asthma. We conducted random effects meta-analysis of mean differences in growth velocity (cm/year) or final height (cm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 39 publications
(47 reference statements)
2
66
0
3
Order By: Relevance
“…This study showed that inhaled corticosteroid therapy affects pubertal growth determining reduced final height in children with asthma and that the growth‐suppression effect is dependent on IC molecule, dose, and duration of the treatment.Our findings on asthma and IC use on height are consistent with other studies reporting that long‐term use of ICs for more than 12 months in asthmatic children is associated with reduction in growth velocity and final height .…”
Section: Discussionsupporting
confidence: 91%
“…This study showed that inhaled corticosteroid therapy affects pubertal growth determining reduced final height in children with asthma and that the growth‐suppression effect is dependent on IC molecule, dose, and duration of the treatment.Our findings on asthma and IC use on height are consistent with other studies reporting that long‐term use of ICs for more than 12 months in asthmatic children is associated with reduction in growth velocity and final height .…”
Section: Discussionsupporting
confidence: 91%
“…Some other studies have demonstrated the therapeutic safety of budesonide inhalation suspension 1013,22,28. A pilot study showed that treatment with short-term high-dose budesonide (1 mg of budesonide, transnasal nebulization twice daily for 14 days) neither suppressed the hypothalamic–pituitary–adrenal axis nor caused any serious side effects in patients with nasal polyps 10.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 16 RCT showed that ICS use for [12 months in children significantly reduced growth velocity at 1-year follow-up [108]. Final adult height showed a mean reduction of -1.20 cm with budesonide versus placebo in a high-quality RCT by Kelly et al [109].…”
Section: Growth Suppression In Childrenmentioning
confidence: 99%